Pengendalian Syariah Dalam Upaya Meningkatkan Disiplin Kerja Pegawai pada PT. PADERONA MEDAN - P Pardomuan Siregar (SI-MEN, 2019)
This research aims to know the Islamic Control in an attempt to improve the discipline of work employees at PT. Paderona terrain, as well as to know or no influence among Islamic control performed in an attempt to improve the discipline of employees work at PT. Paderona terrain. These studies use quantitative data. Using the method of data collection the questionnaire, interview and observation and data analysis of simple linear regression by using koefesien and the determination of the test t. The results showed that the control of Islamic influence in efforts improve work discipline employees at PT. Paderona terrain. It can be seen from the results of linear regression analysis Y = 1,647 + 0, 934X. This means that when the control of Shariah increased 1% then the discipline of work employees will be increased by 93.4% when other factors are considered fixed (constant). Based on hypothesis testing obtained test results of the determination coefficient obtained Rsquare 89.